The earl's reluctant proposal - Allen, Louise, 1949- (Allen, Louise, 1949- Liberated ladies, 2021)
"Max Fenton, Earl of Burnham, needs someone to attend a house party with him to keep an eye on his willful, romantically inclined stepsister. Though he must have taken leave of his senses when he persuades his sister's prickly piano teacher, Miss Lucy Lambert, into the job! Especially when they are inadvertently compromised together...and his only option is a much more permanent proposal!"--Provided by publisher.